Uncovering genetic determinants of antioxidant properties in Thai landrace rice through genome-wide association analysis - Putut Rakhmad Purnama; Pipob Suwanchaikasem; Supaporn Junbuathong; Somsong Chotechuen; Peerapon Moung-Ngam; Waraluk Kasettranan; Chanita Paliyavuth; Monnat Pongpanich; Sittiruk Roytrakul; Luca Comai; Teerapong Buaboocha; Supachitra Chadchawan (Scientific Reports, 2025)
Abstract Pigmented rice (Oryza sativa L.) is recognized as a source of natural antioxidant compounds, such as flavonoids, oryzanol, tocopherol, and anthocyanin. Because of their nutritional benefits, anthocyanin-enriched or pigmented rice varieties are feasible alternatives for promoting human health. Pigment biosynthesis in rice is a complex process that involves multiple biosynthetic and regulatory genes. This study aimed to identify the genes associated with antioxidant traits in local Thai rice and develop molecular markers for breeding programs. Single nucleotide polymorphisms (SNPs) in 233 rice cultivars, 119,541 SNPs from the promoters, and the first 5 exons of all genes were associated with antioxidant phenotypes determined using 2,2’-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid), 2,2-diphenyl-1-picrylhydrazyl, ferric reducing antioxidant power, total flavonoid content, and total phenolic content assays through a mixed linear model (MLM) genome-wide association study (GWAS). GWAS analysis detected 336 quantitative trait nucleotides located at 93 loci, 83% of which were consistently mapped to the reported quantitative trait loci of antioxidant traits. Ten loci, including the OsRc gene, were consistently co-associated with all phenotypic traits. Two genetic markers for polymerase chain reaction detection were developed for the OsTT8 gene and the OsRc promoter, both of which were positively correlated with antioxidant properties. These markers can be applied for antioxidant trait selection in rice breeding programs.